Targeting BRAF Mutant Colorectal Cancer: Progress in Combination Strategies - Sundar, Raghav (Cancer Discov, 2017)
BRAF mutations in colorectal cancer portend a poor prognosis, with first-line treatment often involving triplet or quadruplet chemotherapy, and single agent targeted therapy with BRAF inhibitors failing to demonstrate clinical activity. Blockade of multiple critical nodes along the MAPK and other pathways may be necessary to improve response rates and survival.